2016
DOI: 10.1111/jomf.12308
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence in Gay and Lesbian Family Relationships

Abstract: Intergenerational ambivalence—the simultaneous presence of both positive and negative dimensions of a parent–child tie—is a concept widely used in family studies. Scholars have clarified the measurement of psychological ambivalence, or an individual’s own feelings of ambivalence towards others. Yet research has yet to demonstrate whether—and, if so, how—individuals characterize others as ambivalent. Moreover, relatively little is known about ambivalence in gay and lesbian families. In the present study 60 in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 63 publications
(147 reference statements)
1
43
0
2
Order By: Relevance
“…Reczek's () study on ambivalence in gay and lesbian family relationships provides insights into how discrimination may operate differently for LG families than ethnic minority families. Specifically, LG individuals experience discrimination tied to family structure (e.g., “You should marry someone of the opposite sex”), whereas other minority families are less likely to experience discrimination based on family formation.…”
Section: Model Of Family Resilience For Lg Familiesmentioning
confidence: 99%
“…Reczek's () study on ambivalence in gay and lesbian family relationships provides insights into how discrimination may operate differently for LG families than ethnic minority families. Specifically, LG individuals experience discrimination tied to family structure (e.g., “You should marry someone of the opposite sex”), whereas other minority families are less likely to experience discrimination based on family formation.…”
Section: Model Of Family Resilience For Lg Familiesmentioning
confidence: 99%
“…The ambivalence of their social standing as couples may reverberate across the family network when other family members make efforts to claim the legitimacy of a family member's gay or lesbian relationship (Connidis, 2003). Recent research identified mid‐life gay and lesbian couples' perceptions of the ambivalent views and actions of other family members regarding their sexual identity and same‐sex relationship (Reczek, ). Exploring both the actual ambivalence experienced by family members of LLAT partners and LLAT partners' perceptions of ambivalence on behalf of family members would help us to better understand the relational character of ambivalence.…”
Section: Proposed Research Agendamentioning
confidence: 99%
“…Still others may feel ambivalent about their belonging in states that articulate or even legislate heteronormativity. Life events such as partnering and raising children could heighten ambivalence during adulthood (Connidis, ; Hosking et al, ; Reczek, , ). In addressing these various forms of ambivalence, we seek to answer Connidis's () call to examine the ambivalence occurring in LGBTQ‐parent families at multiple levels beyond the family unit itself.…”
Section: Life Course Perspectives On Adult Children Of Lgbtq Parentsmentioning
confidence: 99%
“…They may choose to avoid talking about their parents in the company of those who have more conservative views (e.g., older generations) or in more formal settings, such as work or religious spaces, where talking about sexuality—however indirectly—might be perceived as inappropriate or even controversial (Reczek, ). Others may feel resentful that disclosing their parents' identities tasks them with the responsibility of educating others and advocating for social justice, even when they have no difficulties in the context of their own parent–child relationships (Reczek, ). Life course analysis can provide an understanding of these complexities by exploring how families are entrenched in a culturally and politically interlaced “range of scales from the home and community to the city and region” (Valentine, Skelton, & Butler, , p. 481).…”
Section: Life Processes Among Adults Who Have Lgbtq Parentsmentioning
confidence: 99%
See 1 more Smart Citation